Analysis of Annual Spt Reporting Article 21 Before and After the Implementation of the E-Filling System at PT Surya Toto Indonesia, Tbk - Wahyuni, Efa; Kuncara, Tommy (DINASTI RESEARCH, 2024)
The purpose of this research is to understand and gather information on how the employees of PT. Surya Toto Indonesia fulfill their obligations as taxpayers in reporting their Annual Income Tax Return (SPT) for PPh 21, to identify the advantages and disadvantages of the e-filing system, and to explore several efforts to overcome the challenges associated with this system. It also aims to examine the differences in reporting the Annual Income Tax Return (SPT) for PPh 21 before and after the implementation of the e-filing system. The data processed in this research is sourced from primary data, which includes qualitative data from interviews and the company profile of PT. Surya Toto Indonesia, Tbk, and quantitative data related to the calculation of PPh 21 on irregular income for employees. The findings of this study indicate that the employees of PT. Surya Toto Indonesia have fulfilled their obligations as taxpayers in reporting the Annual Income Tax Return for PPh 21. In the implementation of the e-filing system, there are both advantages and disadvantages. Differences have been noted before and after the implementation of the e-filing system in terms of the Notification Letter Form (SPT), tax calculation procedures, time/place effectiveness, efficiency, archiving, data submission of the SPT, and taxpayer compliance.